Analysis of informal social networks of friendship, trust and learning in a restaurant - Braga, Natalia Lopes; Carvalho, Renata Guimarães de; Martins, José Wilton Lima; Matos, Tereza Glaucia Rocha; Maciel, Regina Heloisa; Lopes, Isabele Pequeno (Revista de Administração da UFSM, 2020)
Purpose – The objective of the research was to analyze informal social networks that are part of the informal organization of a restaurant, specifying relational and structural aspects of the networks of friendship, trust and learning established amongst its workers. Design/methodology/approach – The approach of Social Networks Analysis was used, which adopts as a principle the perspective that the actors and their actions are interdependent and they establish connections amongst themselves. The study counted on the participation of 24 workers from a restaurant in the city of Fortaleza-CE, Brazil, whose social networks were mapped and analyzed with the help of Ucinet and NetDraw software. Findings – As a result, it was found that informal networks are quite active in the restaurant. Their formation and functioning are part of the work culture of the informal organization, and do not necessarily have a direct association with formal positions and sectors. Informal organization assumes a certain independence from the formal structure, but not entirely, since the configuration of the friendship, trust and learning networks are associated with the dynamics of the restaurant's operation and the relevance of the activities performed by the workers. Originality/value – The research shows that the analysis of social networks allows a better understanding of the relationships established between workers, as well as the intermediated content, formation of informal groups, identification of actors who are leaders and mapping of information flows, contributing to the understanding of the informal organization of work.